Porous carbon foam loaded CoSe2 nanoparticles based on inkjet-printing technology as self-supporting electrodes for efficient water splitting. (10th January 2023) - Wang, Yingxue; Yu, Jing; Liu, Qi; Liu, Jingyuan; Chen, Rongrong; Zhu, Jiahui; Li, Rumin; Wang, Jun
Highlights: Inkjet printing technology was used to deposit ZIF-67 nanoparticles on melamine foam. Porous carbon foam loaded CoSe2 was prepared by pyrolysis and subsequent selenization. CoSe2 /CMF with good flexibility was directly used as working electrode with good stability. CoSe2 /CMF shows excellent HER and OER performances in alkaline media. Abstract: Reasonable design of self-supporting electrocatalyst with porous structure and flexibility is very important for hydrogen and oxygen evolution reactions. Herein, we constructed porous carbon foam loaded CoSe2 (CoSe2 /CMF) as self-supporting electrode by combining inkjet printing, pyrolysis and selenization technologies. The non-contact and precise control characteristics of inkjet printing nano-deposition technology reduces the accumulation of CoSe2 nanoparticles on porous carbon foam, having access to full exposure for active edge sites. Due to the outstanding intrinsic catalytic activity, abundant electrochemical active sites and high electrical conductivity, in alkaline media, CoSe2 /CMF exhibits outstanding electrocatalytic behavior in hydrogen evolution and oxygen evolution reactions, with low overpotentials of 122.6 and 400.0 mV at 10 mA cm −2, respectively, lower than CoP/CMF and CoO/CMF, highlighting the advance of selenides in electrocatalysis. This study is helpful to the design of high-efficiency self-supporting electrocatalysts for water splitting. Graphical abstract: Image, graphical abstract